Characterization of water from the river watershed Lonqueador evaluated for parameters physical, chemical and microbiology - Calegari, Rubens Perez; Boffe, Panthy Michelle; Piloto, Cynthia de Azevedo; Tessaro, Dinéia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This research was conducted with the objective of carrying out the physicochemical and microbiological diagnosis of the Lonqueador river's water located in the town of Francisco Beltrão. The physicochemical and microbiological aspects were collected and analyzed at three points along the Lonqueador river being them: east, central point and the river source, respectively. Water quality was assessed by indicators established by CONAMA Resolution 357/2005, being: water temperature, pH, dissolved oxygen, turbidity, BOD, total coliforms, Escherichia coli and thermotolerant. The results evaluated for physical and chemical parameters meet the legislation, except biochemical oxygen demand, indicating generally good quality of the Lonqueador river's water to maintain its basic functions for aquatic life. Regarding the microbiological aspects, showed the presence of total coliforms and Escheria coli in points assessed, except the source, demonstrating the effects of human action on the quality of the watercourse.